2014
DOI: 10.1115/1.4027653
|View full text |Cite
|
Sign up to set email alerts
|

Predictions of Transient Flame Lift-off Length With Comparison to Single-Cylinder Optical Engine Experiments

Abstract: A state-of-the-art, grid-convergent simulation methodology was applied to three-dimensional calculations o f a single-cylinder optical engine. A mesh resolution study on a sector-based version o f the engine geometry further verified the RANS-based cell size recommendations previously presented by Senecal et al. ("Grid Convergent Spray Models for Internal Com bustion Engine CFD Simulations," ASME Paper No. ICEF2012-92043). Convergence o f cylinder pressure, flame lift-off length, and emissions was achieved fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…These Lagrangian-Drop, Eulerian-Fluid spray and mixing models have been shown by previous researchers to be sensitive to the Eulerian grid resolution (Abani et al, 2008;Wang et al, 2010;Dempsey et al, 2012). Research has shown that using a model setup similar to this one, results in acceptable grid convergence of the lift-off length and reaction zone thickness for a diesel spray with cell sizes of 0.35 mm (Senecal et al, 2013a;Senecal et al, 2013b;Pomraning et al, 2014). Thus, this was used as the minimum cell size in this work.…”
Section: Computational Fluid Dynamics Modelingmentioning
confidence: 99%
“…These Lagrangian-Drop, Eulerian-Fluid spray and mixing models have been shown by previous researchers to be sensitive to the Eulerian grid resolution (Abani et al, 2008;Wang et al, 2010;Dempsey et al, 2012). Research has shown that using a model setup similar to this one, results in acceptable grid convergence of the lift-off length and reaction zone thickness for a diesel spray with cell sizes of 0.35 mm (Senecal et al, 2013a;Senecal et al, 2013b;Pomraning et al, 2014). Thus, this was used as the minimum cell size in this work.…”
Section: Computational Fluid Dynamics Modelingmentioning
confidence: 99%
“…These grid settings have been shown to yield good agreement with test data in previous studies performed internally at Caterpillar which have looked at several key outputs including liquid and vapor penetration as well as LOL, fuel and soot distributions. Furthermore, past studies [36][37][38][39] have shown that using a CONVERGE model setup similar to the one described in this work results in acceptable grid convergence of the lift-off length and reaction zone thickness for a diesel spray with cell sizes of 0.35 mm. Accordingly, similar settings resulting in a minimum cell size of 0.35 mm were used for the current study as well.…”
Section: Htpv Simulation Methodologymentioning
confidence: 77%
“…The fluid computational domain encompassed the full engine geometry including the intake and exhaust manifolds as shown in the Appendix (Figure A2). The mesh details and various simulation parameters, including model specifications for spray atomization and evaporation, were based on the methodology described in Senecal et al 24 Briefly, the spray is initially represented as liquid droplets (blobs) comparable to the orifice diameter, droplet atomization proceeds according to the Kelvin-Helmholtz and Rayleigh-Taylor (KH-RT) instability model, and collisions are predicted by the no-time-counter (NTC) method. 24 Spray parameters for the rate shape, start of injection and injection duration were specified based on the experimental data.…”
Section: Resultsmentioning
confidence: 99%